Systematic Review of Patients Presenting With Suspected Myocardial Infarction and Nonobstructive Coronary Arteries. Issue 10 (10th March 2015) - Pasupathy, Sivabaskari; Air, Tracy; Dreyer, Rachel P.; Tavella, Rosanna; Beltrame, John F.
<x xml:space="preserve">Abstract</x> Background— Myocardial infarction with nonobstructive coronary arteries (MINOCA) is a puzzling clinical entity with no previous evaluation of the literature. This systematic review aims to (1) quantify the prevalence, risk factors, and 12-month prognosis in patients with MINOCA, and (2) evaluate potential pathophysiological mechanisms underlying this disorder. Methods and Results— Quantitative assessment of 28 publications using a meta-analytic approach evaluated the prevalence, clinical features, and prognosis of MINOCA. The prevalence of MINOCA was 6% [95% confidence interval, 5%–7%] with a median patient age of 55 years (95% confidence interval, 51–59 years) and 40% women. However, in comparison with those with myocardial infarction associated with obstructive coronary artery disease, the patients with MINOCA were more likely to be younger and female but less likely to have hyperlipidemia, although other cardiovascular risk factors were similar. All-cause mortality at 12 months was lower in MINOCA (4.7%; 95% confidence interval, 2.6%–6.9%) compared with myocardial infarction associated with obstructive coronary artery disease (6.7%, 95% confidence interval, 4.3%–9.0%). Qualitative assessment of 46 publications evaluating the underlying pathophysiology responsible for MINOCA revealed the presence of a typical myocardial infarct on cardiac magnetic resonance imaging in only 24% of patients, with myocarditis occurring in 33% and no significant abnormality in 26%. Coronary artery spasm was inducible in 27% of MINOCA patients, and thrombophilia disorders were detected in 14%. Conclusions— MINOCA should be considered as a working diagnosis with multiple potential causes that require evaluation so that directed therapies may improve its guarded prognosis.